Ventilator Weaning Through Spontaneous Breathing Trials in Children with Tetralogy of Fallot in the PICU: A Case Report - Megah Fitrian; Kadek Ayu Erika; Muhammad Yunus (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Tetralogy of Fallot (TOF) is a congenital heart defect that causes chronic low oxygen levels, increased right ventricular workload, and a higher risk of complications. Weaning mechanical ventilation in patients with TOF is particularly challenging due to right ventricular dysfunction, muscle weakness, and the risk of heart failure. This study evaluates the use of a spontaneous breathing trial (SBT) strategy with pressure support ventilation (PSV) mode for mechanical ventilation weaning in pediatric patients with TOF. An observational study was conducted on a six-year-old pediatric patient with TOF and a cerebral abscess who underwent mechanical ventilation weaning using the SBT technique with PSV mode. The patient’s vital signs (heart rate and respiratory rate) and oxygen saturation were monitored 24 h before, during, and 24 h after the trial. Weaning was successfully completed within 11 h without signs of failure, such as hypoxemia or muscle fatigue. The rapid shallow breathing index measured prior to weaning was within an acceptable range. The patient’s physiological parameters remained stable throughout the process, and no Tet spells were observed. These findings suggest that SBT combined with PSV mode is a viable weaning strategy in pediatric TOF cases, particularly when a longer trial duration is used. However, because this report is based on a single case, the results should be interpreted with caution and cannot be generalized to all patients with TOF.